Impact of Pandemic COVID-19 on the knowledge and attitude of hand hygiene among medical graduates - Rajkumar N.; S. Khaja Moinuddin (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Hand hygiene is one of the most important measures among infection control practices. Knowledge of hand hygiene among medical graduates crucial in minimizing nosocomial infections. During the pandemic COVID-19, awareness is being created through various routes concerning hand hygiene to combat the pandemic. The current study targeted at determining the impact of awareness programs on hand hygiene awareness among medical graduates.Materials and Methods: This was a cross-sectional study based on a questionnaire to evaluate the knowledge of hand hygiene among second-year graduate medical students. The structured questionnaire was sent to the participants through the email and Whatsapp in the form of a google doc link. The degree of knowledge of hand hygiene was determined by dividing the responses into three classes based on a score of more than 75% considered good, 50-74% moderate, and 50% considered poor as less than. Individual responses received and the data analyzed.Results: A total of 95 students were included in the study. Out of these 54 (56.84%) were females and 41 (43.16%) males. A preponderance of knowledge level was found to be good (87%) among the participants. It has been observed that the majority of students had a positive attitude towards hand hygiene (98-100%).Conclusion: It was noticed from the results obtained in this study, that a significant rise in the knowledge levels and positive attitude among medical graduates during pandemic COVID-19.